Assessment of long-term air pollution impacts on soil properties in the vicinity of Arnot power station on the South African highveld - Van Tienhoven, Anne Mieke (Department of Geological Sciences, 2016)
Atmospheric pollution on the South African high veld is perceived as a concern because of the combination of heavy industry and climatic features that prevail in the region. The frequent occurrence of surface inversions (80 - 90 % of days in the winter months), permits the accumulation of pollutants near ground level. Although industrial stacks, and those of power stations in particular, are generally able to emit gaseous and particulate pollutants above the boundary layer, looping and fumigation of plumes may occur under convective conditions. Under such circumstances, the concentration of pollutants at ground level may be high, especially within 4 km of the stack. Since considerable damage to European and North American ecosystems has occurred as a result of atmospheric pollution, concerns were first raised in a report by Tyson, Kruger and Louw in 1988, that similar effects may be taking place on the eastern highveld region of South Africa. The current study was prompted in direct response to these concerns. The first major objective was to establish long-term monitoring sites whereby changes in the pedosphere in response to atmospheric inputs could be detected. The second objective was to characterise the soil collection and to determine whether any impacts are detectable at this early stage. Arnot power station was selected as the focal point of the study as it is a base-load power station, is the most distant from the industrial centres of Witbank, Middelburg and Gauteng and has been in operation for over twenty years. Fifteen sampling sites located in an arc ranging ENE to SE downwind of the power station were selected. Both topsoil and subsoil were sampled at each site. Details of geographical co-ordinates and site features were noted to enable reproducible resampling. Sampling took place in August 1996, but three sites were visited again in October and resampled to test the reproducibility of sampling. Although not statistically comparable, the soils of each site showed similar results for key analyses, which included EC, pH, organic carbon and acid neutralising capacity.